Relevansi Nilai Informasi Arus Kas dengan Rasio Laba Harga dan Perubahan Laba Harga Sebagai Variabel Moderasi: Hubungan Nonlinier - Astuti Sri Sumarni; Rahmawati Rahmawati (Jurnal Akuntansi dan Auditing Indonesia, 2007)
The objective of this study is to examine the moderating impact of earnings price ratio and change in earnings price ratio on the information content of cashflows. This study used cashflows information from 41 samples of manufacture firms listed in Jakarta Stock Exchange during 1999 until 2002.Hypothesis state that there are relationship between cashflows and stock return if they are moderated with earnings price ratio and also change in earnings price ratio, are examined by Nonlinear Least Square Regression that significant at 5%. Assumption classic tests are done, there are normality test with Jarque-Bera (JB) test of normality, linearity test with scatterplot, heterosce¬dasticity test with White Heteroscedasticity test, and autocorrelation test with Durbin-Watson test.The results of assumption classic shows that samples are not normal distributed and nonlinear, the results also shows that there are some problems heteroscedasticity but can be repaired with white heteroscedasticity consistent variance and standard error. The result of hypothesis examination shows that if they are moderated with earnings price ratio and also change in earnings price ratio, cashflows have information content in nonlinear model. Cashflows data that moderated with earnings price ratio have information relevant before, at the publication date and after publication date of financial statement, but cashflows data that moderated with change in earnings have information relevant before and at the publication date of financial statement.Keyword:    cashflows, earnings price ratio, change in earnings price ratio, stock return